Comparative evaluation of different methods to quantify proteinuria in preeclampsia - Kannali, Pavani; Akki, Poornima; S., Nafeesa Farheen (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Worsening of condition in preeclampsia is indicated by progressive proteinuria, hence its quantification helps in decision making and plan treatment accordingly. The present study was undertaken to compare different methods of estimation of proteinuria to find best method for quantification. Methods: It was a hospital based prospective study conducted on a group of 100 pregnant women diagnosed as preeclampsia after 20 weeks of gestation, they were subjected to different methods of quantification of proteinuria after admission in department of obstetrics and gynaecology, Narayana medical college and hospital, Nellore over a period of one year. Results: Present study showed strong positive strength of association of SSA test was higher compared to the spot urinary PCR and spot urinary dipstick. To assess the predictability of three methods compared against 24-hour urine protein estimation by ROC curve. The AUC of the SSA test and spot urinary PCR was stronger than the urinary dipstick. Study showed a significant better method as SSA>>Urinary PCR>>dipstick with accuracy of 96.04%, 95.0% and 54% respectively. Conclusions: This study concluded that spot urine SSA and urine PCR are reliable investigations compared to dipstick method. So, spot urine SSA and urine PCR can be used for detection of proteinuria in pregnant women with pre-eclampsia with high accuracy, which is more rapid than time consuming 24-hour urine protein estimation. Thus, this quick method with high accuracy is very useful to prevent feto-maternal morbidity and mortality in India.